The Influence of Self-Esteem, Rewards, and Work Ethic on Productivity - Syahputra, Fadli Angga Reza; Chandra Jaya, Rama; Dadan Abdul Aziz Mubarok (Dinasti Publisher, 2023)
Every company must have goals that must be achieved, one of the strengths possessed bya company to achieve goals is to increase employee productivity. PT ABS , which is engaged in the garment sector, is inseparable from the human resources in the company, needs to pay attention to aspects to increase productivity, self-esteem, appreciation and work ethic of the company so thatcompany activities run optimally. The purpose of this study was to determine the effect of SelfEsteem, Appreciation and Work Ethic on Employee Productivity of PT ABS Production Division. The research method used is quantitative research method with descriptive and verification approaches. The results showed that: (1) Work Productivity of employees of PT ABS Production Division in thecategory of less good. (2) Employee Work Self-Esteem of PT ABS Production Section in the category of less good (3) Awards of PT ABS Production Section in the category of less good. (4) The Work Ethic of PT ABS Production Section is in the poor category (5) Partially Self-esteem has a positive influence on Employee Work Productivity. (6) Partially, appreciation has a positive influence on employee productivity. (7) Partially Work Ethic has a positive influence on Employee Productivity.(8) Partially Simultaneously Self-Esteem, Appreciation and Work Ethic have a positive influence onWork Productivity.